Phorbol ester inhibits furosemide-sensitive potassium transport in BALB/c 3T3 preadipose cells. - O'Brien, T G (1983)
The tumor promoter phorbol 12-myristate 13-acetate (PMA) rapidly decreased the rate of 86Rb+ uptake into BALB/c 3T3 preadipose cells. The component of total 86Rb+ influx affected by PMA is insensitive to ouabain but sensitive to the diuretic furosemide. Experiments designed to investigate the characteristics of the K+ transport system sensitive to PMA revealed that: (i) 86Rb+ uptake is highly dependent on external Na+, (ii) 86Rb+ uptake is highly dependent on external Cl-, (iii) 22Na+ uptake is dependent on external K+, and (iv) a major component of 86Rb+ efflux that is sensitive to PMA and furosemide is not dependent on extracellular K+. These features strongly implicate a Na+K+/Cl- cotransport system as the target of PMA and furosemide in these experiments. PMA caused a net intracellular accumulation of K+ within 15 min in these cells, presumably via its inhibitory effect on furosemide-sensitive K+ transport. Within 30 min after PMA treatment, the mean cell volume was significantly reduced in treated compared to control cells, with a maximum decrease of 21% attained at 4 hr after PMA. The significance of these findings for biologic changes induced by PMA is discussed.